Deconstructing and re-constructing the fictional universe - Čale Feldman, Lada (Amfiteater (Ljubljana), 2022)
The paper discusses how the metadramatic modalities of simultaneous deconstruction and reconstruction of the fictional universe figure in two contemporary plays: Pascal Rambert’s The closure of love (2011) and Tim Crouch’s The Author (2009). The discussion reveals that the two much-acclaimed plays belong to a resilient self-reflective line of dramas questioning the closure of representation that starts in the early modern period with such classical pieces as Shakespeare’s Hamlet and Calderón’s The Great Theatre of the World.
Keywords: closure of representation; deconstruction; dekonstrukcija; metadrama; Pascal Rambert; Pedro Calderón de la Barca; Tim Crouch; William Shakespeare; zaprtje reprezentacije